Changes regarding Age and Correlations between Serum Lipids and Body Mass Index in Humankind - Nagashima, K.; Yamasawa, I.; Kamohara, S.; Shiota, M.; Komori, T.; Watanabe, Y.; Nakano, M.; Matsubara, T. (Methods of Information in Medicine, 2002)
Objectives: To improve insight into age and gender related distributions of serum lipids and their correlation with body mass index (BMI).Methods: Serum lipids embracing atherogenic index (AI) and BMI were analyzed from the results obtained in 19,823 men and 14,788 women undergoing a health examination between 1986 and 1996.Results: The changes in total cholesterol (TC), triglyceride (TG), AI and BMI differed regarding gender. Although high-density lipoprotein-cholesterol (HDL-C) showed a flat pattern for all ages in both genders, its level in women was higher than in men. The ratio of the number in the unsuitable range to those in the suitable range increased with age as to TC in both sexes, then more than half of the population have an unsuitable level in the sixth decade. As for the correlation between serum lipids and BMI: TC, TG and AI correlated positively, but HDL-C correlated negatively. There were significant gaps between both age and gender.Conclusions: We suggest that the normal range of values of serum lipids needs to be revised according to gender and age to evaluate the risk status for a cardio-cerebrovascular disease more precisely in the field of preventive medicine. Simpler guidelines are preferable in specialized care as well as in general practice, particularly since computer technology is not yet universally adapted. In the near future, when computed information technology will be as common as the electricity and the telephone are current on the whole earth, all guidelines will have to be computed on the spot and personally.
Keywords: Sexual distinction; cholesterol; guideline; health promotion; risk factor